Perancangan Sistem Manajemen Gudang Tepung di PT X - Mintarto Leopatria; Herry Christian Palit (Jurnal Titra, 2013)
Management system at powder warehouse in PT X still has many problems within. Improvement in management system needs to be done to overcome that problem. The difference between actual product’s amounts and the record, unscheduled planning production, and unorganized warehouse layout are the problem of this company. Improvement for the record of actual product inside warehouse is done to match the record of administration record. This process would be necessary to reduce the gap in stock opname process. MPS can be use to determine the ideal time and the ideal amount of total production for company, so that the inventory cost could be reduced. The result of MPS could reduce the inventory cost in amount of 48.8%. Inventory turn over in the warehouse became better. The day sale in inventory was reduced from 14 days to only 6 days.